Preliminary Economic Study on the Production of ZnO Nanoparticles Using a Sol-Gel Synthesis Method - Fikri Aziz Shalahuddin; Sera Serinda Almekahdinah; Asep Bayu Dani Nandiyanto (Jurnal Kimia Terapan Indonesia, 2019)
The economic evaluation is one of the key points in building chemical industries. This paper presented a preliminary economic evaluation of the large scale production of zinc oxide (ZnO) nanoparticles using the sol-gel method, which is very useful for helping decision whether the fabrication of this material profitable or not. Particularly, the study was done by changing the cost of raw material, which was compared to several economic parameters such as GPM, PBP, and CNPV. The result showed that the project was profitable by increasing raw material cost below 100% from the estimated raw material cost, informing the fact for the prospective fabrication for fulfilling the demand of ZnO nanoparticles.